Determinants of the Export Activity. A Configurational Analysis of the Family Firm - Monreal-Pérez, Joaquín; Ifakhkharen-Rziki, Omar (European Journal of Family Business, 2024)
Family firms are of great importance in the increasingly competitive and unstable environment in which they have to operate. Furthermore, they evidence a series of specific characteristics that make them behave differently –specifically, when having to export. Among these distinctive traits, their lack of resources and more conservative attitude towards risk may limit their international activity. Nevertheless, we show that these obstacles are minimized when considering certain determinants that have traditionally been seen as drivers of firms’ export competitiveness (i.e. innovation, collaboration, using own means, export promotion mechanisms, and exporting to developed markets) together as a set. We perform a Fuzzy-set Configurational analysis to study the configurational effect of the abovementioned determinants on a sample of 68 Spanish family firms in the agricultural sector.